Terjemah sunan at Tirmidzi - Abu Isa Muhammad bin Isa bin Surah At Tirmidzi (CV. Asy Syifa', 1992)
ir, Jil.2,c.1 ; Jil.3,c.1,ws.jl.3.c.2/tr, jil.1=c.1; jil.2=c.2-3; jil.3=c.3; jil.4=c.1; jil.5=c.1-3/stoc6, jl.1=c.1; jl.2=c.1-2; jl.3=c.1-3; jl.4=c.1; jl.5=c.1-3